2015
DOI: 10.1152/ajpcell.00073.2014
|View full text |Cite
|
Sign up to set email alerts
|

Marine omega-3 fatty acids prevent myocardial insulin resistance and metabolic remodeling as induced experimentally by high insulin exposure

Abstract: Franekova V, Angin Y, Hoebers NT, Coumans WA, Simons PJ, Glatz JF, Luiken JJ, Larsen TS. Marine omega-3 fatty acids prevent myocardial insulin resistance and metabolic remodeling as induced experimentally by high insulin exposure. Am J Physiol Cell Physiol 308: C297-C307, 2015. First published December 4, 2014 doi:10.1152/ajpcell.00073.2014.-Insulin resistance is an important risk factor for the development of several cardiac pathologies, thus advocating strategies for restoring insulin sensitivity of the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…Furthermore, higher n-6/n-3 PUFAs ratio and low serum concentration of EPA and DHA in severe psoriasis, confirmed in our group of patients, may play important role in the development of comorbidity. Several studies in rat and mouse models of induced heart failure have reported that intake of EPA and DHA prevent left ventricular remodeling and contractile dysfunction [14]. Energy-restricted diet enriched in n-3 PUFA has protective effect on metabolic markers and clinical outcome in psoriatic patient with obesity [19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, higher n-6/n-3 PUFAs ratio and low serum concentration of EPA and DHA in severe psoriasis, confirmed in our group of patients, may play important role in the development of comorbidity. Several studies in rat and mouse models of induced heart failure have reported that intake of EPA and DHA prevent left ventricular remodeling and contractile dysfunction [14]. Energy-restricted diet enriched in n-3 PUFA has protective effect on metabolic markers and clinical outcome in psoriatic patient with obesity [19].…”
Section: Discussionmentioning
confidence: 99%
“…As in the CD-fed group, the hormone significantly induced the translocation of FAT/CD36 to the plasma membrane. Recently, in isolated rat cardiomyocytes incubated under insulin resistance evoking conditions, Franekova et al [ 41 ] demonstrated that the inclusion of EPA and DHA to the medium prevented the persistent translocation of CD36 to the sarcolemma and protected the metabolic and functional properties of the cardiomyocytes. In this regard, we previously demonstrated that the administration of dietary fish oil to SRD-fed rats was able to reverse heart muscle lipotoxicity and benefit key enzyme activities involved in the glucose metabolism [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the evidence points to association of the early CD36 dysfunction observed with high fat feeding with an increase of postabsorptive insulin levels [60, 61]. Treatment of isolated rat cardiomyocytes with high insulin for 48h results in insulin resistance with persistent relocation of CD36 to the plasma membrane while inclusion of omega-3 polyunsaturated FA in the medium prevents this relocation and the onset of insulin resistance [62]. Posttranslational regulation of CD36 includes its ubiquitination, with opposite effects of FA and insulin [63], its glycosylation which was found altered in the heart of the spontaneously hypertensive rat [64] as well as its acetylation, palmitoylation, etc [3].…”
Section: How Does Cd36 Facilitate Fa Uptake?mentioning
confidence: 99%